Psikoedukasi Peran Komunikasi Orangtua Guna Mengoptimalkan Pengasuhan Anak di Desa Petaonan - Zahra Aulia Rahman; Meidwiana Nur Azizah; Ika Tri Jumrotus Sholikah; Cyndhira Detya Mayvanesya; Ni Putu Rizky Arnani; Hapsari Puspita Rini (FKIP Universitas Mataram, 2026)
Communication in parenting carried out by parents is an important aspect in the family. Parental communication is a key factor in shaping parenting patterns and the psychological development of children, whether they are in early childhood, adolescence, or adulthood. Family communication is very important for maintaining harmony within the family. If families communicate well, a harmonious family will be formed, which allows for the preservation of harmony within the family and vice versa. The parent-child communication patterns that occur within the family context vary greatly from one family to another. However, there are still many parents who apply one-way, authoritarian communication, or are less responsive to their children's emotional needs, which affects both the children and the parents. Therefore, education for the community is needed regarding the importance of effective communication in parenting. This community service aims to educate mothers in the Petaonan Village area, averaging around 30-40 years old, with a total of 20 participants. The method of implementing the activity includes three stages: planning, execution, and evaluation. The results of the questionnaire given before and after this activity show that the average score before was 78.75 and after was 85.15. The observation results indicate that during the implementation process, participants showed enthusiasm and engagement in the presentation of the material provided. This is evident from the participants who asked various questions related to their experiences during parenting. Therefore, this activity not only provides technical strategies for communicating with children of different ages but also raises participants' awareness of the importance of communication strategies in parenting.